A Tour in the Archaeological Site of Choirokoitia Using Virtual Reality: A Learning Performance and Interest Generation Assessment - Christofi, Maria; Kyrlitsias, Christos; Michael-Grigoriou, Despina; Anastasiadou, Zoe; Michaelidou, Maria; Papamichael, Ioanna; Pieri, Katerina (My University, 2018)
Virtual Reality (VR) application of the archaeological site of Choirokoitia has been designed and developed. The virtual reconstruction of the site simulates its current structure and is based on real data acquisition. The VR application allows the participants to virtually navigate through the archaeological site and acquire historical information for various important points of it. This study assesses the learning performance of the application’s users and their interest for the topic. Findings demonstrated a strong significant improvement in learning performance of the users with the change in their interest following a bell-shaped distribution. This indicates that the developed VR application can be used as a teaching tool for Cultural Heritage purposes.
Keywords: Cultural heritage; Learning assessment; Virtual heritage; Virtual reality; Virtual worlds